Shaping Visitor Movement: The Role of Interior Elements In Galeri Nasional Indonesia - Shafa Dzikra Kamila; Wendy Sunarya (Journal of Architectural Research and Design Studies, 2025)
Variations in interior elements, such as colour, lighting, spatial scale, and exhibition layout, can create distinct spatial atmospheres that influence how visitors perceive and behave in gallery settings. This study investigates the relationship between interior spatial qualities and visitor movement in the Indonesian National Gallery. Employing a qualitative observational approach, the research involved direct documentation of visitor paths, time spent in each room, types of activities, and spatial preferences. Eight gallery rooms were evaluated based on observable interior characteristics, including ceiling and wall colours, lighting contrast, spatial layout, and display arrangement. The findings reveal that certain interior qualities, such as smooth lighting contrast, open circulation, and balanced display arrangements, encourage more extended stays and interactive behaviors like lingering and photography. In contrast, high visual contrast, clustered displays, or enclosed layouts may prompt visitors to move more quickly through the space. This study also demonstrates the value of combining qualitative spatial judgments with behavioural observations to explore how design elements influence visitor experience. While exploratory, the method provides a framework for further research in evaluating gallery design to create more engaging and emotionally resonant spatial experiences.